2007
DOI: 10.2337/dc07-0564
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Gestational Diabetes in Women Receiving Prophylactic 17α-Hydroxyprogesterone Caproate for Prevention of Recurrent Preterm Delivery

Abstract: OBJECTIVE -Progesterone has a known diabetogenic effect. We sought to determine whether the incidence of gestational diabetes mellitus (GDM) is altered in women receiving weekly 17␣-hydroxyprogesterone caproate (17P) prophylaxis for the prevention of recurrent preterm birth.RESEARCH DESIGN AND METHODS -Singleton gestations in women having a history of preterm delivery were identified from a database containing prospectively collected information from women receiving outpatient nursing services related to a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 17 publications
2
59
3
1
Order By: Relevance
“…Accordingly, it seems especially relevant to evaluate the potential effects of progesterone-based medications on mother and foetus. Considering the diabetogenic effect of progesterone, Rebarber et al (2007) reported that the use of 17a-hydroxyprogesterone caproate (17P), in the micromolar range, by women having a history of preterm delivery, increased the risk of development of GD. Another study involving women of hispanic descent with no previous history of diabetes showed that the use of an injectable progestagen-based contraceptive for long periods of time was associated with an increased risk of developing GD (Xiang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it seems especially relevant to evaluate the potential effects of progesterone-based medications on mother and foetus. Considering the diabetogenic effect of progesterone, Rebarber et al (2007) reported that the use of 17a-hydroxyprogesterone caproate (17P), in the micromolar range, by women having a history of preterm delivery, increased the risk of development of GD. Another study involving women of hispanic descent with no previous history of diabetes showed that the use of an injectable progestagen-based contraceptive for long periods of time was associated with an increased risk of developing GD (Xiang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that apoptosis is involved in the pathophysiology of type 1 and 2 diabetes and also contributes to the involution of the b-cell mass in the postpartum phase (Scaglia et al 1995), we first proposed the hypothesis that progesterone might be involved in b-cell death, also contribute to the development of gestational diabetes (GD). Both progesterone's diabetogenic effect and its potential to induce b-cell death require attention with the increasing pharmacological use of progestagens throughout pregnancy for prevention of recurrent preterm delivery (Sanchez-Ramos et al 2005, Dodd et al 2008, Jayasooriva & Lamont 2009), which has been correlated to the enhanced incidence of GD (Rebarber et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While in general progesterone is known to exhibit diabetogenic properties, early reports are conflicting as to whether the use of 17OHPC increases a woman's risk for the development of gestational diabetes (GDM) [6][7][8]. These conflicting results may be related to differences in study design or particularly in maternal characteristics of the populations.…”
Section: Introductionmentioning
confidence: 62%
“…Rebarber et al retrospectively compared 557 patients receiving 17OHPC for preterm labor prophylaxis to 1524 controls who similarly had a history of preterm delivery. The frequency of gestational diabetes in the 17OHPC group was 12.9% versus 4.9% for the controls (OR 2.9 (95% CI 2.1-4.1)) [6]. Interestingly, while overall no differences were observed in the use of maintenance tocolysis, fewer patients in the 17OHPC group received beta agonists for tocolysis (18%) versus no controls (25.1%) ( < 0.002).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation